Sistem Pendukung Keputusan Pemilihan Sumber Mata Air Terbaik Dengan Metode Topsis (Studi Kasus Depot Talago) - Amelia, Dhella; Randa, Dimas Dwi; Sentosa, Rio Bayu; Gusriva, Revi; Putra, Yeviki Maisyah (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Spring sources play a crucial role in meeting clean water needs, especially for the operational sustainability of the Talago Depot. Selection of optimal spring sources is a strategic aspect in ensuring adequate water quality and availability. This research aims to develop a Decision Support System (DSS) using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to assist Talago Depot in selecting the best spring source. A Decision Support System (DSS) or Decision Support System (DSS) is a system that is able to provide problem solving capabilities and communication capabilities for problems with semi-structured and unstructured conditions. There are many problems that can be used as research in a decision support system, one of which is determining the best spring source. In this research, a decision making system will be designed using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The TOPSIS method is a multi-criteria decision making method that uses the principle that the selected alternative must have the closest distance to the positive ideal solution and the furthest distance to the negative ideal solution. It is hoped that this research can make a practical contribution to the efficiency of decision making regarding the selection of spring sources at the Talago Depot. With this SPK, it is hoped that Depot Talago can make more informed and measurable decisions, increase operational sustainability, and have a positive impact on clean water services to the surrounding community. The results obtained from this research are data on the best spring sources.